An analysis of policy levers used to implement mental health reform in Australia 1992-2012. Issue 1 (June 2015) - Grace, Francesca; Meurk, Carla; Head, Brian; Hall, Wayne; Carstensen, Georgia; Harris, Meredith; Whiteford, Harvey
Abstract Background Over the past two decades, mental health reform in Australia has received unprecedented government attention. This study explored how five policy levers (organisation, regulation, community education, finance and payment) were used by the Australian Federal Government to implement mental health reforms. Methods Australian Government publications, including the four mental health plans (published in 1992, 1998, 2003 and 2008) were analysed according to policy levers used to drive reform across five priority areas: [1] human rights and community attitudes; [2] responding to community need; [3] service structures; [4] service quality and effectiveness; and [5] resources and service access. Results Policy levers were applied in varying ways; with two or three levers often concurrently used to implement a single initiative or strategy. For example, changes to service structures were achieved using various combinations of all five levers. Attempts to improve service quality and effectiveness were instead made through a single lever-regulation. The use of some levers changed over time, including a move away from prescriptive, legislative use of regulation, towards a greater focus on monitoring service standards and consumer outcomes. Conclusions Patterns in the application of policy levers across the National Mental Health Strategy, as identified in this analysis, represent a novel way of conceptualising the history of mental health reform in Australia. An improved understanding of the strategic targeting and appropriate utilisation of policy levers may assist in the delivery and evaluation of evidence-based mental health reform in the future.